Evaluation of the Therapeutic Potential of Mesenchymal Stem Cells (MSCs) in Preclinical Models of Autoimmune Diseases - Radha Krishan Shandil; Saumya Dhup; Shridhar Narayanan (Hindawi Limited, 2022)
Autoimmune diseases, chronic in nature, are generally hard to alleviate. Present long-term treatments with available drugs such as steroids, immune-suppressive drugs, or antibodies have several debilitating side effects. Therefore, new treatment options are urgently needed. Stem cells, in general, have the potential to reduce immune-mediated damage through immunomodulation and T cell regulation (T regs) by inhibiting the proliferation of dendritic cells and T and B cells and reducing inflammation through the generation of immunosuppressive biomolecules like interleukin 10 (IL-10), transforming growth factor-β (TGF-β), nitric oxide (NO), indoleamine 2,3-dioxygenase (IDO), and prostaglandin E2 (PGE2). Many stem cell-based therapeutics have been evaluated in the clinic, but the overall clinical outcomes in terms of efficacy and the longevity of therapeutic benefits seem to be variable and inconsistent with the postulated benefits. This emphasizes a greater need for building robust preclinical models and models that can better predict the clinical translation of stem cell-based therapeutics. Stem cell therapy based on MSCs having the definitive potential to regulate the immune system and control inflammation is emerging as a promising tool for the treatment of autoimmune disorders while promoting tissue regeneration. MSCs, derived from bone marrow, umbilical cord, and adipose tissue, have been shown to be highly immunomodulatory and anti-inflammatory and shown to enhance tissue repair and regeneration in preclinical models as well as in clinical settings. In this article, a review on the status of MSC-based preclinical disease models with emphasis on understanding disease mechanisms in chronic inflammatory disorders caused by exaggerated host immune response in rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE) was carried out. We also emphasized various factors that better predict the translation of stem cell therapeutic outcomes from preclinical disease models to human patients.